Human resources estimates and funding for antibiotic stewardship teams are urgently needed - Pulcini,C; Morel,CM; Tacconelli,E; Beovic,B; de,With K; Goossens,H; Harbart,S; Holmes,AH; Howard,P; Morris,AM; Nathwani,D; Sharland,M; et al. (Clinical Microbiology and Infection, 2017)
Antibiotic stewardship (AS) teams are essential actors for combating antibiotic-resistant bacteria in healthcare and community settings, and are routinely mentioned in national and international guidelines, recommendations and action plans. Usually, AS teams in resource-rich settings are multidisciplinary, made up of different experts, commonly including infectious diseases (ID) specialists, clinical microbiologists and pharmacists, adequately trained in antibiotic prescribing and stewardship [1].